Hopeful and Concerned: Public Input on Building a Trustworthy Medical Information Commons. Issue 1 (March 2019) - Deverka, Patricia A.; Gilmore, Dierdre; Richmond, Jennifer; Smith, Zachary; Mangrum, Rikki; Koenig, Barbara A.; Cook-Deegan, Robert; Villanueva, Angela G.; Majumder, Mary A.; McGuire, Amy L.
A medical information commons (MIC) is a networked data environment utilized for research and clinical applications. At three deliberations across the U.S., we engaged 75 adults in two-day facilitated discussions on the ethical and social issues inherent to sharing data with an MIC. Deliberants made recommendations regarding opt-in consent, transparent data policies, public representation on MIC governing boards, and strict data security and privacy protection. Community engagement is critical to earning the public's trust.